Optically addressable array of optomechanically compliant glass nanospikes on the endface of a soft-glass photonic crystal fiber - Wang, Zheqi; Xie, Shangran; Jiang, Xin; Babic, Fehim; Huang, Jiapeng; Pennetta, Riccardo; Köhler, Johannes; Russell, Philip St. John (ACS Photonics, 2019)
Arrays of elongated nanoscale structures with suitable optical and mechanical properties can act as probes of numerous physical processes at the nanoscale, with applications in for example high-resolution optical imaging and atomic force microscopy. They can also be used to investigate optomechanical phenomena such as synchronization among large assemblies of mechanical oscillators. Here we report a novel and versatile technique for fabricating two-dimensional light-guiding arrays of mechanically compliant glass nanospikes with lengths up to several hundred μm. The procedure starts with a multicore fiber made by stacking and drawing capillaries and rods of two different germanate glasses with markedly different acid etching rates. After a suitable etching step, a free-standing nanospike array is created at the fiber end-face. The parameters are chosen so that there is evanescent coupling between adjacent nanospikes, which gives rise to strong optomechanical forces that can be exploited to drive and control the mechanical motion of the nanospikes and thus the optical properties.
CRIS-Team Scopus Importer:2019-10-18
Keywords: Multicore fiber; Nanospike array; Optical forces; Optomechanics; Soft-glass fiber

Sustained Self-Starting Orbital Motion of a Glass-Fiber "nanoengine" Driven by Photophoretic Forces - Xie, Shangran; Pennetta, Riccardo; Wang, Zheqi; Russell, Philip St. John (ACS Photonics, 2019)
Controllable optically driven rotation of microscopic objects is desirable in many applications, but is difficult to achieve. Here we report a sustained self-starting orbital motion of a clamped elongated nanostructure, a glass-fiber nanospike, when a CW laser beam is focused axially onto its tip. Analysis shows that photophoretic antitrapping forces, acting on the nanospike with a delayed response, introduce optomechanical gain into the mechanical motion, overcoming the intrinsic mechanical dissipation and resulting in growth from noise of oscillations at the resonant frequency of the nanospike. These photophoretic forces further enable phase-locking of the orthogonal fast and slow vibrations of the nanospike (induced by slight mechanical anisotropy), giving rise to a self-sustained orbital motion. The locked phase of orbital motion can be changed by tuning the gas pressure and adjusting the geometrical asymmetry of the system. This light-driven nanoengine opens up a new degree of freedom for controlling the rotational motion of elongated nano-objects.
CRIS-Team Scopus Importer:2019-12-20
Keywords: fiber nanospike; nanomotor; optomechanics; orbital motion; photophoretic force